A quasi-zero-stiffness vibration isolator using bi-stable hybrid symmetric laminate. (1st November 2022) - Li, Ming; Li, Yanqi; Liu, Xiaohui; Dai, Fuhong
Abstract: The quasi-zero-stiffness (QZS) vibration isolator is usually composed of positive and negative stiffness elements in parallel. The negative stiffness element usually requires specific constraint boundaries to form negative stiffness characteristics, which cannot meet the lightweight design of spacecraft structures. So the bi-stable hybrid symmetric laminate (BHSL) is presented as a negative stiffness element. A finite element model (FEM) is developed to carry out static and dynamic analyses of this vibration isolator. An equivalent theoretical model is developed based on the restoring force–displacement curve of BHSL. The approximate analytical solutions and direct numerical solutions are obtained by employing the averaging method and the Runge-Kutta method, respectively. Different types of the steady-state response are obtained, namely the symmetrical multi-harmonic response, the asymmetric multi-harmonic response and the single-harmonic response. There exists a small gap between the analytical solutions and the Runge-Kutta solutions or the FEM results only at the low frequency excitation due to the super-harmonics. The displacement transmissibility is used to quantify the vibration isolation performance of this vibration isolator. The experiment is designed to verify the theoretical and FEM models from static and dynamic analysis perspectives. The results show adjusting geometric parameters and lay-up designs can improve the vibration isolation performance.